Assessment of human papillomavirus awareness in association with head and neck cancer at a screening event. (8th July 2017) - Berger, Michael H.; Cohen, Erin R.; Shamrock, Alan G.; Chan, Brandon; Camp, Michelle; Lo, Kaming; Sargi, Zoukaa B.
Abstract : Objectives/Hypothesis: To assess the baseline awareness of human papillomavirus (HPV) infection as a cause of head and neck cancer (HNC) to design improved targeted screening and education efforts. Study Design: Retrospective review of collected survey at a cancer screening event. Methods: This was a screening event at three hospitals and one community center in Miami, Florida. Participants were recruited throughout the Greater Miami area. Descriptive statistics were used to summarize the demographic characteristics of those who were aware of HPV and those who were not. Adjusted odds ratios, odds ratios, and χ 2 tests were used in statistical analysis. Results: A total of 196 women and 112 men were screened across four sites, with 187 participants at hospital‐based events and 124 participants at the community‐based event. Forty percent of respondents had heard of HPV, and 28.0% identified HPV as a risk factor for HNC. Non‐Hispanic and Hispanic respondents were 3.309 and 2.445 times, respectively, more likely than Haitian respondents to have heard of HPV. Women were 2.488 times more likely than men to be aware of HPV. College graduates were 2.268 times more likely than those with less than a college degree to be aware of HPV. Younger respondents were more likely to be aware of HPV. Of those who identified HPV as a risk factor for HNC, 95.4% also correctly identified smoking and 75.9% also correctly identified alcohol as risk factors. Conclusions: Disparities in HPV and HNC awareness were noted between gender, age, education level, and ethnicity. Level of Evidence: NA. Laryngoscope, 128:386–392, 2018